Talent Management And Academic Workforce Research In Higher Education: A Bibliometric Review - Moh. Badrut Tamam (Har Press Indonesia, 2026)
Research on talent management and the academic workforce in higher education has expanded across multiple disciplinary areas, yet the literature remains conceptually dispersed and lacks an integrated bibliometric synthesis. This study aims to map the development, intellectual structure, and emerging themes of talent management and academic workforce research in higher education. A bibliometric review was conducted using the Scopus database, with data retrieved through the TITLE-ABS-KEY field and refined through a staged screening process. The final sample comprised 650 English-language journal articles published between 2015 and 2025. The analysis combined performance analysis and science mapping to examine publication trends, influential contributors, collaboration patterns, and thematic evolution. The findings show that the field has grown steadily, with an annual growth rate of 13.04%, indicating increasing scholarly attention to the strategic role of academic talent in higher education. The literature is interdisciplinary and widely distributed across journals, institutions, and countries, although author collaboration remains relatively fragmented. Conceptually, the field has evolved from traditional personnel and workforce concerns toward broader and more strategic themes, including leadership, job satisfaction, work engagement, well-being, workload, and institutional sustainability. These results suggest that talent management in higher education is increasingly understood as a multidimensional institutional strategy for attracting, developing, supporting, and retaining academic staff. This study contributes by providing a comprehensive intellectual map of the field and offering directions for future research on sustainable academic workforce management in higher education.